INCREASE MOTIVATION IN A FOREIGN LANGUAGE LESSON WITH THE HELP OF SONG LYRICS - Bystrai,; Zasedateleva,; Belova,; Shtykova,; Orlova, (Revista Inclusiones, 2020)
Knowing foreign languages is becoming a leading factor in social adaptation in modern society, but mastering foreign languages is accompanied by a number of difficulties: the long process of assimilation of new knowledge, confrontation with many linguistic and speech phenomena that do not occur in the native language, insufficient knowledge of the realities of life of the country whose language is being studied. As a result, students are becoming less and less interested in mastering the language. The application of songs in studying foreign languages makes this process more effective